A practical guide to mental health & learning disorders for every educator : how to recognize, understand, and help challenged (and challenging) students succeed - Cooley, Myles L. (Free Spirit Publishing, 2018)
"Using clear, jargon-free language, this accessible, ready-to-use reference helps all educators--whether in inclusive classrooms, general education settings, or other environments--recognize mental health issues and learning disabilities that are often observed in students. Covering topics including PTSD, bipolar disorder, autism spectrum disorder, and many others, the book explains how each disorder or difficulty might be exhibited in the classroom and offers straightforward suggestions for what to do (and what not to do). Fully revised and updated to correspond to the DSM-5, this edition addresses newly diagnosed disorders, as well as incorporating the latest research and interventions for existing disorders. The book also includes current information about educational practices such as creating a culturally responsive classroom and supporting students' social-emotional learning. Digital content includes customizable forms from the book, and a free downloadable PLC/Book Study Guide is available at freespirit.com/PLC"